Development of Prescribing-safety Indicators for GPs using the RAND Appropriateness Method - Avery, Anthony J; Mulvaney, Caroline; Serumaga, Brian; Spencer, Rachel; Campbell, Stephen M (British Journal of General Practice, 2011)
In the UK, a process of revalidation is being introduced to allow doctors to demonstrate that they meet current professional standards, are up-to-date, and fit to practise. Given the serious risks to patients from hazardous use of medicines it will be appropriate, as part of the revalidation process, to assess the safety of prescribing by GPs.
Keywords: consensus; safety; medication errors; primary health care